Response mapping to translate health outcomes into the generic health-related quality-of-life instrument EQ-5D: Introducing the mrs2eq and oks2eq commands - Manuel Ramos-Goni, J; Rivero-Arias, O; Dakin, H (2013)
Reliable and accurate mapping techniques that translate health-related quality-of-life data into EQ-5D index values are now in demand by researchers conducting economic evaluation of health care technologies. In this article, we present two commands (mrs2eq and oks2eq) that translate data from two widely used disease-specific instruments into EQ-5D index values and predicted probabilities of being at a particular level on each EQ-5D domain. mrs2eq conducts a response mapping approach to transform data from the stroke-specific modified Rankin scale into index values from the generic quality-of-life EQ-5D instrument. oks2eq uses a response mapping model to estimate EQ-5D index values based on patients' responses to the Oxford Knee Score. © 2013 StataCorp LP.